Pengaruh Servant Leadership, Motivasi Kerja dan Lingkungan Kerja terhadap Kepuasan Kerja pada Karyawan - Latansya Ardiawan; Trisnia Widuri; Kukuh Harianto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to determine and analyze the influence of Servant Leadership, Work Motivation, and Work Environment on Employee Job Satisfaction at the Jimbun Medika Inpatient Primary Clinic. The background of this research is based on the phenomenon observed in the field, where employee job satisfaction levels show frequent fluctuations. These fluctuations have the potential to impact not only individual productivity but also the overall quality of healthcare services provided to patients. The research method used is a quantitative approach with a survey technique as the primary data collection method. The population in this study includes employees of the Jimbun Medika Inpatient Primary Clinic, with data collected using structured questionnaires. The data were analyzed using statistical tools, including multiple linear regression analysis, to determine the effect of the independent variables on the dependent variable. The research findings indicate that Servant Leadership (X1), when tested partially, does not have a significant effect on employee job satisfaction. In contrast, Work Motivation (X2) and Work Environment (X3) each show a positive and significant influence on employee job satisfaction. Furthermore, when analyzed simultaneously, all three independent variables—Servant Leadership, Work Motivation, and Work Environment—have a significant combined effect on job satisfaction levels among employees at the clinic. These findings suggest that to improve employee satisfaction and ultimately enhance service quality, the management of Jimbun Medika should prioritize improving motivation and providing a supportive work environment, while also re-evaluating leadership strategies to better align with employee needs and expectations.